AB0217 Construct validation of the italian version of the 5-item compliance questionnaire for rheumatology (I-CQR5). (12th June 2018) - Azzolina, D.; Ometto, F.; Raffeiner, B.; Botsios, C.; Favero, M.; Astorri, D.; Friso, L.; Gregori, D.; Done, J.; Doria, A.
Abstract : Background: The 5-item Compliance Questionnaire for Rheumatology (CQR5) allows the identification of patients likely to be high adherers (HA) to anti-rheumatic treatment (i.e. taking ≥80% of their medications correctly), or "low" adherers (LA). 1 Objectives: The objective was to validate the construct of an Italian version of CQR5 in rheumatoid arthritis (RA). Methods: Cross-cultural adaptation comprised: forward translation, synthesis of the translations, back-translation, expert committee assessment and field-testing. Validation was conducted administering the adapted version (I-CQR5) to RA patients (disease duration >1 year, treated with ≥1 self-administered disease-modifying anti-rheumatic drug, capable of completing the questionnaire unaided) on one occasion. Questionnaires were anonymous but contained self-reported data. Construct validity and reliability were assessed with Rasch analysis (Partial Credit model Parametrisation, PCM). Martin-Loef Likelihood ratio test assessed invariance for gender, age, education, social status and disease duration. Results: The adaptation process was closed by the expert committee assessment. I-CQR5 is reported in Figure 1. Among 604 patients, 274 were included in the validation process, 6 questionnaires were incomplete. Median age was 57 years (48–67), females were 201 (77%), disease duration was 13.5 years (8.8–19.3), most patients lived with partner/family (159, 75%) and had a middle/secondary school education (184, 69%). HA were 93 (67%) and LA 179 (35%). Factor analysis revealed ordered thresholds in most items, 2 factors were sufficient to explain variability (Chi-square=0.46, p=0.5) (Tab.1). Item-fit statistics showed overall agreement of items with parametrisation (Infit statistics=0.6–1.4; excluding item no.5). Chi-square showed agreement with PCM parametrisation by item (excluding the item no.1). Martin-Loef likelihood ratio test confirmed unidimensionality (Chi-square 65.8, df=53, p=0.11) and Separation Reliability Index confirmed internal consistency (Patient Separation Index 0.91) (Tab.1). I-CQR5 was invariant to age (Chi-square=40.6, df=28, p=0.059), education level (Chi-square=49.9, df=42, p=0.187), social status (Chi-square=10.5, df=15, p=0.79), disease duration (Chi-square=13.6, df=36, p=0.220); Martin-Loef test was significant for gender (Chi-square=25.4, df=14, p=0.031). Conclusions: I-CQR5 was well understood by patients and construct validity, unidimensionality and internal consistency were confirmed by factor analysis and PCM. Reference: [1] Hughes L, et al. A 5 item version of the Compliance Questionnaire for Rheumatology (CQR5) successfully identifies low adherence to DMARDs. BMC Musculoskelet Disord2013;14:286. Disclosure of Interest: None declared